Capacitation of stakeholders on CSA, CIS and One-Health approaches - Attuquaye, Victor; Duah, Solomon Agyeman; Oppong-Mensah, Birgitta; Martey, Francisca; Damba, Osman Tahidu; Nikoi, Gordon; Yeboah, Stephen; Adomako, Joseph; Kyere, Reginald; Dalaa, Mustapha Alasan (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
In order to establish and go on to strengthen CSA-CIS and One-Health Innovation Platforms at the AICCRA project intervention communities, there is the need to train relevant intermediary stakeholders to understand the One-Health concept and how it can be boosted with climate-smart agriculture innovations and integrated climate services for agriculture. These intermediary stakeholders comprise of municipal/district agriculture directors, crop officers, extension officers, and lead farmers. Their understanding of these concepts will contribute to mainstreaming them into their day-to day activities and sharing the knowledge beyond the AICCRA intervention communities.